Overview Faktor Penentu Nilai Perusahaan - Agustin, Isni; Annisa, Arna Asna (Journal of Accounting and Digital Finance, 2021)
This research aims to analyze the effect of debt-to-equity ratio, return on asset, and current ratio on firm value as measured by economic value added. This research is quantitative research with use regression analysis. This research used secondary data sourced from the annual report of Islamic commercial banks for 2015–2020. The population in this research was 14 Islamic commercial banks in Indonesia for 2015-2020. The sample selection in this study uses purposive sampling to ensure 11 Islamic commercial banks. The results found that the debt-to-equity ratio has a negative and insignificant effect on firm value, return on assets has a positive and significant effect on firm value. The current ratio has a positive and significant effect on firm value. Meanwhile, Islamic social reporting can moderate the relationship between debt-to-equity ratio and return on assets to firm value but cannot moderate the current ratio and firm value.